High power non-electrolytic capacitor LED driver with three ports based on energy distribution. Issue 1 (1st December 2022) - Li, Zejun; Zhang, Junzhao; Xu, Bingshe; Han, Xiaoqing; Li, Fan; Lu, Xiaofeng
Abstract: To eliminate the influence of electrolytic capacitors on the driving life of high-power LED, a three-port high-power LED without electrolytic capacitor driving power supply based on energy distribution is proposed. The energy difference between the input terminal and the output terminal is balanced by the auxiliary DC-DC circuit to reduce the ripple of the output current. The working principle of the topology and switching mode is analyzed in detail. According to the proposed circuit topology, the mechanism of the output current ripple of the low-frequency circuit is analyzed, and a low-frequency ripple control strategy suitable for the circuit topology is proposed. The specific implementation scheme and the key parameters of the circuit design are given, and the model is verified, which proves that the proposed model is feasible.